Finance and Sustainability Proceedings from the Finance and Sustainability Conference, Wroclaw 2017 (Springer Proceedings in Business and Economics,, 2018)
This volume covers the proceedings of the ZAFIN Finance and Sustainability conference, organized by the Wroclaw University of Economics in cooperation with the Corvinus University of Budapest and the University of Economics in Prague. The authors analyze a variety of issues related to recent finance problems, including corporate finance, public finance, monetary and fiscal policy issues, and risk management. The book also discusses topics related to sustainable finance, the transition to green economies, corporate sustainability and sustainable development. The target audience for this book includes researchers at universities and research and policy institutions, graduate students, and practitioners in economics, finance and international economics working for private or government institutions.